OPTIMIZATION PROBLEM OF EMERGENCY FACILITY LOCATIONS IN A DISASTER AREA WITH RANDOM VULNERABILITIES - Sholeha, Risatianti
This thesis examines the problem of locating emergency facilities in a disaster area with random disaster vulnerability. The location chosen and the number of emergency facilities opened are required to be able to serve the affected disaster victims. This problem can be viewed as a location placement optimization problem which will be solved using the Tabu Search algorithm. The data used is taken from the area around the Lembang Fault. Our simulation results provide several potential locations to be used as locations for emergency facilities for disaster victim services.